2014
DOI: 10.3945/ajcn.113.080168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral magnesium supplementation on physical performance in healthy elderly women involved in a weekly exercise program: a randomized controlled trial , ,

Abstract: Daily magnesium oxide supplementation for 12 wk seems to improve physical performance in healthy elderly women. These findings suggest a role for magnesium supplementation in preventing or delaying the age-related decline in physical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
3
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 29 publications
4
103
3
6
Order By: Relevance
“…Dhingra and colleagues showed a direct correlation between hypomagnesemia and respiratory muscle function in humans (25), and Stendig-Lindberg and colleagues demonstrated that maximum isometric voluntary contraction force was significantly weaker in hypomagnesaemic subjects (26, 27). These and other recent studies (28) show that magnesium deficiency directly and significantly impacts muscle strength in general and respiratory muscle strength specifically. As Matias and colleagues explain, magnesium deficiency has a significant effect on muscle performance, probably due to the key role of magnesium in energetic metabolism, transmembrane transport, muscle contraction, and on the cellular level on Na-K ATPase, Na–K–Cl co-transport, K channels, charge screening, and permeability effects on membranes (29).…”
supporting
confidence: 80%
“…Dhingra and colleagues showed a direct correlation between hypomagnesemia and respiratory muscle function in humans (25), and Stendig-Lindberg and colleagues demonstrated that maximum isometric voluntary contraction force was significantly weaker in hypomagnesaemic subjects (26, 27). These and other recent studies (28) show that magnesium deficiency directly and significantly impacts muscle strength in general and respiratory muscle strength specifically. As Matias and colleagues explain, magnesium deficiency has a significant effect on muscle performance, probably due to the key role of magnesium in energetic metabolism, transmembrane transport, muscle contraction, and on the cellular level on Na-K ATPase, Na–K–Cl co-transport, K channels, charge screening, and permeability effects on membranes (29).…”
supporting
confidence: 80%
“…The cutoffs for dividing the sample into tertiles were 10 and 11 points in men, and 9 and 11 points in women. Since the 4 m walking speed and five times sit-to-stand test are independent predictors of several negative outcomes in older people 24,25 , these parameters were also considered as separate items in this analysis. The cutoffs used for the 4 m gait speed were 0.83 and 0.98 m/s in males, and 0.72 and 0.85 m/s in females; for the five times sit-to-stand test, the corresponding cut-offs were 11.2 and 9.4 in males, and 10.2 and 12.6 s in females.…”
Section: A Physical Performance Testsmentioning
confidence: 99%
“…As a result, overweight women had significantly stronger grip strength in both hands, and women who exercised had significant associations of grip strength with BMD (3). It is important to highlight that both studies were conducted in elderly women, similar to the study by Veronese et al (1). From this evidence we can argue that bone density is an important cofactor related to physical performance in this specific population.…”
mentioning
confidence: 60%
“…Veronese et al (1) recently published an article entitled "Effect of oral magnesium supplementation on physical performance in healthy elderly women involved in a weekly exercise program: a randomized controlled trial" in a recent issue of the Journal.…”
mentioning
confidence: 98%